Glycated hemoglobin and microalbuminuria in patients with type 2 diabetes mellitus - Afrim Zeqiraj; Dafina Zeqiraj; Teuta MullaGoga; Fidel Krasniqi; Agim Shabani; Sanije Berisha; Agim Berisha; Blerim Morina; Florjana Zogaj (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. In recent decades, type 2 diabetes mellitus (DM) has become the most prevalent disease worldwide. In the coming decades, a large number of people are expected to be affected by this disease, it is spreading rapidly in an epidemic in some countries due to the aging of the population, which will increase the cost for health care providers, especially in countries with poorer health. Microalbuminuria is the earliest stage of progressive kidney damage, the simplest and most reliable predictor for assessing the probability of overt nephropathy in diabetes. The purpose of the study was to investigate the relationship between duration of diabetes and higher microalbumin secretion. Material and methods. Blood samples were collected after an overnight fast of 10–12 hours, EDTA-Sarstedt tubes were used to collect blood from patients and analyze glycated hemoglobin (HbA1c) levels, while blood samples collected in Sarstedt S-monovette tubes were used for serum (to analyze other biochemical parameters). Samples were centrifuged, aliquoted and stored at 4 °C until analysis. The urine sample (24 h urine) was analyzed for microalbumin (immunoturbidimetric method). All analyzes were performed with Roche-Integra 400 Plus equipment at the Polyclinic and Laboratory Alpha in Peja. This prospective study was conducted in the Dukagjin Plain in the Republic of Kosovo. Statistical analysis: data were entered into Microsoft Excel data sheet and analyzed using SPSS version 22 software. Results. The average age of the participants in the study was 48.00 ± 2.34 years (range 26–79) compared to the control group — 41.00 ± 2.65 years (range 20–65), the percentage of women was higher (58.33 %) than men (41.66 %). From the analyzes made between the patients under study and the control group, we obtained high results to a significant degree in these parameters: HbA1c (p < 0.001), triglycerides (p < 0.04), microalbumins (p < 0.001), body mass index (p < 0.03). Conclusions. Increasing levels of microalbuminuria in diabetic patients worldwide and in ours will be an immediate requirement for microalbuminuria tests to be routinely performed in addition to HbA1c by all health institutions for better surveillance of patients in order to prevent the deterioration of their health status.